Further evaluation of latency-based brief functional analysis methods: An evaluation of treatment utility. (3rd March 2016) - Falcomata, Terry S.; Muething, Colin S.; Roberts, Garrett J.; Hamrick, Jennifer; Shpall, Cayenne
Abstract: Objective : Objectives were to evaluate latency-based brief functional analysis (BFA) model for identifying functions of aberrant behavior and treatments generated based on the results of the latency-based brief functional analysis. Methods : We conducted latency-based BFA, including contingency reversals, and function-based treatment evaluations, including non-contingent reinforcement (NCR) and differential reinforcement of alternative behavior (DRA) with three individuals with autism using single subject design methodology. Results : Socially-mediated functions (attention; tangible) were indicated for two participants and an automatic function was identified for one participant. The treatments generated based on results of the BFA were effective at reducing aberrant behavior for all participants. Conclusions : Results provide additional support that latency-based BFA model has utility in (a) the identification of functions of aberrant behavior and (b) the generation of function-based treatments. These results suggest clinicians who encounter setting and client-specific constraints (e.g. time; severity of aberrant behavior) have additional flexibility in choosing assessment tools.